Variation in the Shapes of Coronoid Process of Dry Human Mandible of Gujarat Region - Nirali Chavda1 , Priyanka Sharma2 , Kinjal Jethva3 , Kantilal Parmar4 , Hetal Vaishanani 5, A.R.Gand (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Coronoid process is single the bony processes of the ramus of the mandible. It is a thin, triangulareminence, which is flattened from side to side. It differ in shape and size. The importance of frequency in theshapes of Coronoid process is important for maxillofacial surgeons as a graft material as well as for anthropologistsfor the detection of races.Aim: To determine the different shape of Coronoid process of mandible in both sides.Materials and Method: The Present study was conducted on 50 mandibles from the department of Anatomy,Baroda Medical College, Baroda. Variations in the shapes were observed, and photographs were taken.Results: Triangular shape of Coronoid process was most prominent as compare to hook and round shape.Triangular shaped Coronoid was seen in 70% shaped (Type: I) followed by Rounded shaped 26%, Hookshaped was least 4% respectively.Conclusion: This study will be helpful for maxillofacial surgeons, anatomists, forensic researchers,anthropologists.